insígnia, escafandro, sátira e locus: analysis of creative processes in comprovisation (Orfeu, 2021)
Our objects of analysis in this article are the musical pieces named insígnia, escafandro, sátira and locus, created by the author. These are considered to be experiments in comprovisation, given the characteristics of their creative processes. Comprovisation, as a recent term in the literature, has no consensus so far; therefore, we gather here possible antecedents, the notions about and practices that seek in comprovisation its characterization. We distinguish two theoretical strains on the subject, and we carry out our own considerations aiming at an understanding of the term from an interconnection of the flows of interpretation and improvisation - these linked to notions of generative processes of performance and the understanding of Falleiros (2012) on the pact. Through traditional tools of analysis, and the notational perspective of Bhagwati (2013), we believe that the resignification of improvised gestures in the analyzed pieces points to the understanding of these as experiments in comprovisation.
Keywords: comprovisation; composition (music); improvisation (music); creative process; performance